Phenolic profiles, bioaccessibility and antioxidant activity of plum (Prunus Salicina Lindl). (May 2021) - Yu, Jiawen; Li, Wu; You, Bangyan; Yang, Shiying; Xian, Wenyan; Deng, Yu; Huang, Wei; Yang, Ruili
Graphical abstract: Highlights: Epicatechin and neochlorogenic acid were the main free phenolics in plum. Catechin and epicatechin were the major bound phenolics. Naringenin-7-O-β-D-glucoside were the most bioaccessible predominant phenolics. Antioxidant capacity positively correlated with total phenolics after digestion. Significant phenolics contributor to antioxidant activity changed after digestion. Abstract: Plum ( Prunus Salicina Lindl) is a rich source of phenolic compounds. However, the bound phenolics and its bioaccessibility and antioxidant activity remain unclear. Hence, the purpose of this study was to determine: 1) phenolic profiles of plum, including both free and bound phenolic fractions, 2) bioaccessibility of phenolic compounds in plum during simulated gastrointestinal digestions, 3) their antioxidant properties. A total of 17 phenolic compounds were identified by UPLC-Q-Exactive Orbitrap/MS with most epicatechin, neochlorogenic acid and procyanidin B2 in the free phenolics fraction, while catechin and epicatechin was the main compounds in the bound phenolics fraction. After the gastrointestinal digestion phase, the most bioaccessible phenolics were quercetin-pentoside (61.64%), cyanidin-3-O-glucoside (43.26%), and naringenin-7-O-β-D-glucoside (42.04%). The antioxidant capacity of both undigested plum and its digested fractions showed a positive correlation with the total phenolics, and with specific individual phenolic compounds such as neochlorogenic acid, epicatechin and procyanidin B2 in undigested plum whereas catechin, neochlorogenic acid, and epicatechin in digested one. The results confirm that bound fraction of plum contribution to the total phenolic content must be taken into account in the assessment of the improving human health effects of plum.